Potret Dakwah dalam Kegiatan KKN STIBA Makassar di Desa Baruga Kabupaten Maros - Mukran H Usman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Baruga Village is a religious community and still adheres to life character of mutual cooperation which is integrated with the customs that characterize the life of the Baruga Village community. The philosophy of life is based on the principle of achieving prosperity with a high work ethic escorted by a spirit of unity and togetherness, even if the people of Baruga Village are overseas. STIBA Makassar Community Service Program (KKN) III was to practice the higher education tri dharma as a form of community service. The method of community service implementation in Baruga Village was started by analyzing the needs of the community by using instruments that were made independently and SOAR analysis. This was useful for identifying problems and developing work program strategies. STIBA Makassar Community Service Program (KKN) III in Baruga Village was started with a Work Program Seminar (SPK), then Training on Taking Care of a Corpse (PPJ), Hospitality and Health Services (SAPK), Religious Children’s Festival (FAS) and Islamic Signs (RRI). The result of this KKN is that it can be seen in terms of knowledge in the community experiencing the development in Islamic insight, especially in terms of proficiency in recognizing hijaiyah letters, makhraj and tajwid in reading the Koran. In terms of skills, it is especially seen from the side of community skills in taking care of a corpse. In terms of attitude, the community already has a high enthusiasm in learning and practicing Islamic knowledge.